Effect of myomectomy on endometrial cavity: A prospective study of 51 cases - Bhandari, Shilpa (J Hum Reprod Sci, 2016)
CONTEXT: Fibroids are the most common tumors of the uterine cavity. Most of them are diagnosed during the reproductive age when the fertility is an important concern for the female. However, complications can occur after removal of fibroid (myomectomy) too for future pregnancy. Though myomectomy has been sighted as a cause of intrauterine adhesions data regarding the effect of myomectomy on endometrial cavity is lacking. AIMS: Evaluate the incidence of intrauterine adhesion formation after myomectomy and to identify the associated factors. MATERIALS AND METHODS: In this prospective observational study, hysteroscopy was done in 51 infertile patients who had undergone myomectomy 3 months before in a tertiary care center from 2012 to 2015. The presence of intrauterine adhesions noted on hysteroscopy was investigated on the basis of size, number, location and type of fibroid removed, along with intraoperative breach of the uterine cavity. STATISTICAL ANALYSIS: Chi-square test was used for the calculating significant difference in frequency of discrete variables in two groups. P < 0.05 was considered significant. RESULTS: Intrauterine adhesions were seen in 11 out of 51 (21.57%) cases. No significant relationship between intrauterine adhesions and type, size or number of fibroid was observed. No statistical difference in the rate of adhesion formation was seen irrespective of breach of the uterine cavity during myomectomy. CONCLUSION: Intrauterine adhesion formation after myomectomy is not related to the type of surgery or the nature of fibroid. However, in all cases desiring fertility postoperative hysteroscopy is highly recommended to diagnose and treat these adhesions early.